Islamic Economic Politics and Policy for the Use of Artificial Intelligence in the Defense Sector - Saputra, Taufik Aris; Kunaifi, Aang (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Artificial Intelligence (AI) is a controversial issue. Technological progress that is in harmony with efforts to create convenience and speed in human work is inevitable, even though it also creates an impact of vulnerability in the existence and function of humanity. It is worth asking how important is the existence and usefulness of AI for humans. What is the concept of AI development from an Islamic political and economic perspective? This article aims to explain the urgency of the existence of AI in national and state life and to describe the concept of state policy from an Islamic political-economic perspective relating to the development of AI. To obtain a comprehensive analysis, this article uses a literature study approach by collecting, categorizing, classifying, and concluding the subject matter. The references used are studies of Islamic economic politics, Islamic jurisprudence rules, and Islamic history, as well as references related to facts about the use of AI. The results of the study show that the use of AI is very urgent for the life of the nation and state for valid, accurate, and fast military information and decision-making. So, the policy of utilizing AI from an Islamic political economic perspective emphasizes its support through state budget allocation in developing information technology and the military industry.